2006
DOI: 10.1080/03004430500092266
|View full text |Cite
|
Sign up to set email alerts
|

Physical punishment as perceived by parents in Russia: implications for professionals involved in the care of children

Abstract: To contribute to a knowledge base about the approach of families in Russia towards implementing physical punishment, a study was conducted with 100 parents in St Petersburg. A majority of the participants indicated that it was legitimate to use some measure of physical punishment. The use of an object as a measure was considered acceptable by one-third of the participants, especially towards children in the age range 5-12. Forty percent of the participants thought that physical punishment should be implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Replicating previous findings, this study found that FSU origin parents employed more physical punishment in their child‐rearing practices than their Israeli counterparts. This finding extends previous findings from research conducted with parents living in the FSU (Berrien et al , ; Shor, ) and among parents from the FSU living in Israel (Shor, ), implying that child‐rearing ideologies and practices adhered to by parents tend to preserve meaningful elements of the original culture (Frankel & Roer‐Bornstein, ; Levine, ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Replicating previous findings, this study found that FSU origin parents employed more physical punishment in their child‐rearing practices than their Israeli counterparts. This finding extends previous findings from research conducted with parents living in the FSU (Berrien et al , ; Shor, ) and among parents from the FSU living in Israel (Shor, ), implying that child‐rearing ideologies and practices adhered to by parents tend to preserve meaningful elements of the original culture (Frankel & Roer‐Bornstein, ; Levine, ).…”
Section: Discussionsupporting
confidence: 86%
“…The FSU culture emphasizes values such as achievement, emotional control, efficiency and organization in their children's development, whereas the Israeli culture emphasizes values such as social competence and autonomy (Rosenthal & Roer‐Strier, ). As a result, there may be widespread legitimacy for the use of corporal punishment toward children among parents in the FSU (Berrien et al , ; Shor, ). Our findings demonstrate a process by which belonging to a culturally different ethnic minority may be related to parental use of harsh discipline, which in turn is associated with children's prosocial behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has examined CP predictors, focusing primarily on the individual characteristics of parents and children (Clément & Chamberland, 2009; Gagne′, Tourigny, Joly, & Pouliot-Lapointe, 2007). Parenting styles, social context, and cultural norms that may affect individual attitudes (Berrien, Aprelkov, Ivanova, Zhmurov, & Buzhicheeva, 1995; Grogan-Kaylor & Otis, 2007; Shor, 2006) were also examined, but to a lesser extent. Some of these studies focused particularly on immigrants (O’Brien, 2010; Regev, Gueron-Selab, & Atzaba-Poriab, 2012; Shor, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent studies of child abuse ‘show clearly that this is [still] a very substantial and serious global problem’ (Krug and others 2002, p. 6). Across geographic and cultural boundaries, multiple studies have found that the great majority of parents believe that hitting children, at least in moderation, is sometimes necessary and has few if any negative effects (Gofin and others 2004; Shor, 2006; Stafford, 2004; Straus, 1994).…”
Section: Child Abuse: Scope Of the Problemmentioning
confidence: 99%